Kinetics of Gene Expression Changes in Equine Fetal Interzone and Anlagen Cells Over 14 Days of Induced Chondrogenesis - Mok, Chan Hee; MacLeod, James N. (Frontiers in Veterinary Science, 2021)
Within developing synovial joints, interzone and anlagen cells progress through divergent chondrogenic pathways to generate stable articular cartilage and transient hypertrophic anlagen cartilage, respectively. Understanding the comparative cell biology between interzone and anlagen cells may provide novel insights into emergent cell-based therapies to support articular cartilage regeneration. The aim of this study was to assess the kinetics of gene expression profiles in these skeletal cell lines after inducing chondrogenesis in culture. Interzone and anlagen cells from seven equine fetuses were isolated and grown in a TGF-β1 chondrogenic inductive medium. Total RNA was isolated at ten time points (0h, 1.5h, 3h, 6h, 12h, 24h, 48h, 96h, 168h, and 336h), and gene expression for 93 targeted gene loci was measured in a microfluidic RT-qPCR system. Differential transcriptional responses were observed as early as 1.5 hours after the initiation of chondrogenesis. Genes with functional annotations that include transcription regulation responded to the chondrogenic stimulation earlier (1.5 – 96 hours) than genes involved in signal transduction (1.5 – 336 hours) and the extracellular matrix biology (3 – 336 hours). Between interzone and anlagen cell cultures, expression levels of 73 out of the 93 targeted genes were not initially different at 0h, but 47 out of the 73 genes became differentially expressed under the chondrogenic stimulation. While interzone and anlagen cells are both chondrogenic, they display clear differences in response to the same TGF-β1 chondrogenic stimulation. This study provides new molecular insight into a timed sequence of the divergent developmental fates of interzone and anlagen cells in culture over 14 days.